OUT-OF-PLANE MOTION OF A THRUST SHEET DURING ALONG-STRIKE PROPAGATION OF A THRUST RAMP: A DISTINCT-ELEMENT APPROACH - Strayer L.M.; Suppe J. (My University, 2002)
Using a 3D distinct-element mechanical modeling program, we examined the nature and magnitude of out-of-plane motion during along-strike propagation of a simple thrust ramp and attendant fault-related folding. Our numerical model was composed of about 83,000 spherical elastic particles that were bonded together to create an initial solid numerical rock mass, capable of macroscopic fracture and faulting in response to displacement loading. The algorithim is fully dynamic and as such allowed for the storage and sudden release of elastic strain energy in the form of seismic events.We induced progressive along-strike fault-growth and attendant non-cylindrical fold development by varying the along-strike friction within a seeded, planar zone of weakness within the aggregate, a zone that was to become the fault. The result was a well-developed, plunging ramp anticline that grew in amplitude and along-strike length as the macroscopic fault propagated from lower to higher friction regions. Lateral fault propagation was relatively rapid compared with shortening, with a ratio of thrust displacement-to-propagation length (K) of 6.5%.Incremental motion of the particles reflected episodic slip at both the laterally propagating fault-tip and along the existing fault. These episodes were characterized by local clusters of outward radiating velocity vectors that propagated at seismic velocities, marking the model equivalents of earthquakes.The finite displacement vectors in the hanging wall were approximately parallel to the far-field transport direction, with a strike-parallel component that ranged from one to two orders of magnitude less than the strike-perpendicular component. Furthermore, about two-thirds of the particles had strike-parallel motion in the direction of fault propagation and fold plunge. Because the far-field, shortening boundary conditions were uniformly perpendicular to fault strike, this component of motion in the plunge direction was apparently due to a topographically-induced, plunge-parallel shear stress. The along-strike motion involved slip on the main fault as well as transient strike slip on minor vertical, sometimes conjugate zones, apparently induced by the increased topographic load.
Keywords: OUT-OF-PLANE MOTION; THRUST SHEET; THRUST RAMP